1999
DOI: 10.1007/s004670050605
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric dialysis and renal transplantation in Kuwait over the past 11 years

Abstract: Data on end-stage renal disease (ESRD) patients and their renal replacement therapy (RRT) were collected retrospectively from the three dialysis centers, the pediatric urology unit, and the organ transplant center of Kuwait. The study period was from 1 January 1986 to 31 December 1996. A total of 61 children, 50 of whom were Kuwaiti nationals, required RRT for ESRD during those 11 years. This gave an average annual incidence rate of 18 per million Kuwaiti children. Glomerulonephritis was the most-frequent unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
2
8
1
Order By: Relevance
“…A CPD program with skilled and motivated dialysis staff, but lacking financial support is a dramatically frustrating situation for patients, their families and the health care staff. In regions where no pediatric RRT infrastructure is available, children are managed in adult dialysis units, which involve potential risk of RRT undercoverage for the very young, even when dialysis is fully government-funded [20]. Developing countries are a very poorly defined category, encompassing countries with a myriad of economic, epidemiologic, demographic conditions and health care systems, with a spectrum of access to RRT ranging from nil to universal [21].…”
Section: Discussionmentioning
confidence: 99%
“…A CPD program with skilled and motivated dialysis staff, but lacking financial support is a dramatically frustrating situation for patients, their families and the health care staff. In regions where no pediatric RRT infrastructure is available, children are managed in adult dialysis units, which involve potential risk of RRT undercoverage for the very young, even when dialysis is fully government-funded [20]. Developing countries are a very poorly defined category, encompassing countries with a myriad of economic, epidemiologic, demographic conditions and health care systems, with a spectrum of access to RRT ranging from nil to universal [21].…”
Section: Discussionmentioning
confidence: 99%
“…[5] In Kuwait, retrospective studies, have shown that GP is the possible underlying etiology for 24% of the 72 patient per million Kuwaiti nationals accepted on renal replacement therapy every year [10] and 44% of the 18 per million Kuwaiti children. [11] To examine the spectrum of GP in Kuwait, we conducted our study in a prospective manner, for a period of seven years, using the mature diagnostic facilities at Al-Amiri renal center, which covers nearly 1/2 of the care of patients with renal diseases in the state of Kuwait.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 61 children, 50 of whom were Kuwaiti nationals, required renal replacement therapy for end-stage renal disease over a period of 11 years [100]. Glomerulonephritis (44 %) was the most frequent underlying disease, while pyelonephritis (including urinary tract anomalies and dysplastic kidneys) occurred in 30 %.…”
Section: Kuwaitmentioning
confidence: 99%